ANALISIS PERBEDAAN FIRM FINANCIAL PERFORMANCE SEBELUM DAN SESUDAH INDONESIA MOST VALUABLE BRANDS PADA PERUSAHAAN BEI - Widiasmara, Anny; Sudrajat, M.Agus (Widya Warta, 2019)
Brand is an intangible asset. Therefore, managing it is not an easy and trivial thing. Willingness in calculating Brand value and learning it is the key to success which is the first step towards a strong and reliable company, Value brand is a key aspect in creating a company's competitive advantage and hence it is important to generate income flows in the future. The purpose of this study was to analyze differences between Financial Performance Before and After Indonesia Most Valuable Brands in IDX Companies This research was conducted at the Indonesia Stock Exchange (IDX) which provided financial report information and annual reports on its official website at www.idx.co.id. This research was conducted before Indonesia Most Valuable Brands in IDX Companies in 2011-2013 and after Indonesia Most Valuable Brands In the IDX Company in 2014-2016, the sample was purposive sampling, a company that consistently entered the Top 10 of Indonesia Most Valuable Brands and was listed on the Stock Exchange from 2014-2016. The company submits financial statements in rupiah, Firm Financial performance variables are proxyed with Current Ratio, Return on Asset, Book Value per share, EBITDA. The data collection technique uses secondary data, paired sample t-test, the results of this study that there are differences in the current ratio, return on assets, book value per share and EBITDA before and after most valuable brands so that previous research stated that brands could increase Firm Financial Performance was received